1999
DOI: 10.2337/diabetes.48.1.158
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced insulin-stimulated activation of phosphatidylinositol 3-kinase in the liver of high-fat-fed rats.

Abstract: Insulin receptor substrate (IRS)-1 and IRS-2, which mediate phosphatidylinositol (PI) 3-kinase activation, play essential roles in insulin-induced translocation of GLUT4 and in glycogen synthesis. In this study, we investigated the process of PI 3-kinase activation via binding with IRS-1 and -2 in liver, muscle, and fat of high-fat-fed rats, a model of insulin-resistant diabetes. In the liver of high-fat-fed rats, insulin increased the PI 3-kinase regulatory subunit p85alpha and the PI 3-kinase activities asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 29 publications
3
61
0
Order By: Relevance
“…The impaired SKM insulin signaling is crucial for systemic insulin resistance and precedes the development of diabetes (DeFronzo & Tripathy 2009, Pagel-Langenickel et al 2010. However, our study showed that HFD exerts minor effects on Irs1 and Glut4 mRNA in SKM compared with the change in WAT, agreeing with a previous report (Anai et al 1999). NEFA uptake by SKM is controlled by both circulating lipid levels and specific transporters, particularly LPL and FAT/CD36 (Koonen et al 2005, Goldberg et al 2009).…”
Section: Discussionsupporting
confidence: 80%
“…The impaired SKM insulin signaling is crucial for systemic insulin resistance and precedes the development of diabetes (DeFronzo & Tripathy 2009, Pagel-Langenickel et al 2010. However, our study showed that HFD exerts minor effects on Irs1 and Glut4 mRNA in SKM compared with the change in WAT, agreeing with a previous report (Anai et al 1999). NEFA uptake by SKM is controlled by both circulating lipid levels and specific transporters, particularly LPL and FAT/CD36 (Koonen et al 2005, Goldberg et al 2009).…”
Section: Discussionsupporting
confidence: 80%
“…Acute intravenous infusion of leptin (46) and high fat feeding (47), which increase leptin levels, have been shown to increase IRS-1-associated PI 3-kinase in liver in vivo, whereas leptin treatment of C 2 C 12 cells in vitro increases IRS-2-associated PI 3-kinase (12). In Fao cells, the leptin-induced alterations in the insulin-stimulated tyrosine phosphorylation of IRS-1 and IRS-2 resulted in corresponding and divergent changes in the association of the p85 subunit of the PI 3-kinase with these substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired insulin-stimulated translocation of GLUT4 to the plasma membrane has been shown in the insulin-resistant obese Zucker rat (13) and in incubated muscle strips from type 2 diabetic subjects (14). In muscles and adipose tissue biopsies from high-fat-fed rats (15) and also in muscles from obese subjects (16), impaired activation of PI 3-kinase has been observed. In a recently published study that investigated the effect of high-fat feeding in normal rats, it was demonstrated that an insulin-mediated but not a contraction-activated pathway for glucose transport was impaired due to reduced translocation of GLUT4.…”
mentioning
confidence: 96%